Perjanjian Advokasi Antara Advokat dengan Klien dan Penentuan Besaran Honorarium - Armono, Yudhi Widyo (CV. Kurnia Grup, 2024)
Under Law No. 18 Year 2003 concerning advocates, advocates in realizing the agreement, shall be guided by Article 1320 of the Civil Code Act, namely: For the validity of a treaty required four conditions: (1). Agreements that bind them. (2). Ability to make an engagement. (3). A certain thing. (4). A cause that is kosher. Pursuant to Article 21 of Law No. 18 Year 2003 concerning advocates, advocates entitled to receive a royalty on legal services has been given to their clients, but the magnitude of nominal honorarium advocacy no default rule. Then the nominal amount of honorarium advocacy depends on (1). Seniority, it would not be possible consumers will provide funds as advocacy honorarium amount equal to the Advocate beginners. Lawyer quality can also be seen from its credibility in the community. (2). The level of difficulty, the more difficult a case will have an impact on the increasing advocacy honorarium to be paid to the advocate. (3). Territory area case, honorarium given client advocacy should be seen also in the coverage area of a case that happened. (4). The value of the disputed object, the high value of the disputed object is directly proportional to the amount of nominal honorarium provided by the client to the advocate.